Britomart Quest Anew, Victorians Revive the Elizabethan Faerie Queene as Campaigns for Women’s Suffrage Intensify - Susan Clayton (Cahiers Victoriens et Edouardiens)
Nineteenth century reeditions and reworkings of the Renaissance The Faerie Queene, can be equated with renewed interest in one of Spenser’s leading protagonists, Britomart, daughter of a knight, who herself passed as one. This Victorian interest in an example of transgenderism coincided with women’s demands for socio-cultural changes. We shall address the questions of links between gender and power, and consider how the past is used to consolidate the present.Our analysis starts by contextualising Victorian revivals of Britomart’ story, paying special attention to a prose adaptation by Mary MacLeod, then assessing these revivals in relation to women’s demands for change, bearing in mind that British suffragettes also looked across the Channel to another female knight-at-arms, Joan of Arc, for a model for their campaigns. Finally we will consider certain cultural implications when such a resurgence interacts with challenges to gender.